Design and implementation of a bluetooth low energy-based local area network for fall detection - Yu, T.; Stamm, A.; Hartanto, R. (Proceedings, 2018)
Falls are harmful to the elderly; therefore, fall detection technologies have been developed by many researchers to help detecting these incidents. The research presented here investigates a Bluetooth Low Energy-based local area network for fall detection. One of the major concerns is not only the detection of a fall incident but also the location where this incident occurred. This research utilizes a fall detection network with three different types of network nodes: alarm node, relay node, and center node. Alarm nodes are worn by the elderly for fall detection; relay nodes are fixed in the target area for receiving the signal from alarm nodes; and the center node is the hub of the detection network. When a fall incident occurs, the alarm node will send out alarm signals which will be passed towards the center node by the relay nodes. The center node forwards the alarm to any iMessage capable device.